Tau-Cofactor Complexes as Building Blocks of Tau Fibrils - Fichou, Yann; Oberholtzer, Zachary R.; Ngo, Hoang; Cheng, Chi-Yuan; Keller, Timothy J.; Eschmann, Neil A.; Han, Songi (Frontiers in Neuroscience, 2019)
The aggregation of the human tau protein into neurofibrillary tangles is directly diagnostic of many neurodegenerative conditions termed tauopathies. The species, factors and events that are responsible for the initiation and propagation of tau aggregation are not clearly established, even in a simplified and artificial in vitro system. This motivates the mechanistic study of in vitro aggregation of recombinant tau from soluble to fibrillar forms, for which polyanionic cofactors are the most commonly used external inducer. In this study, we performed biophysical characterizations to unravel the mechanisms by which cofactors induce fibrillization. We first reinforce the idea that cofactors are the limiting factor to generate ThT-active tau fibrils, and establish that they act as templating reactant that trigger tau conformational rearrangement. We show that heparin has superior potency for recruiting monomeric tau into fibril compared to any constituent intermediate or aggregate “seeds”. We show that tau and cofactors form intermediate complexes whose evolution toward ThT-active fibrils is tightly regulated by tau-cofactor interactions. Remarkably, it is possible to find mild cofactors that complex with tau without forming ThT active species, except when an external catalyst (e.g. a seed) is provided to overcome the energy barrier. In a cellular context, we propose the idea that tau could associate with cofactors to form a metastable complex that remains “inert” and reversible, until encountering a relevant seed that can trigger an irreversible transition to -sheet containing species.